Geometria analítica nos livros didáticos: uma análise do modelo epistemológicos dominante para o ensino de cônicas no ensino médio - BORGES, Thays de Souza (Universidade Federal do Pará, 2023)
The objective of this work is to carry out an investigation into high school books from public schools in Pará, in order to identify the dominant epistemological model in exposing the content of analytical geometry, in particular, the study of the geometry of conics, taking it yves chevallard's (1999) anthropological theory of didactics (TAD) and the reference epistemological models developed by Benito (2019), in his doctoral thesis, were used as reference. The adopted methodology was the bibliographical qualitative research. The choice of books was made according to their acquisition in the public network and based on the National Textbook Program (2020). We also seek to carry out a survey of scientific studies, such as those of: Macena (2007), Oliveira (2011), Siqueira (2016) and Jesus (2017), to understand how the learning of conic figures develops in High School . Regarding the performed analyses, we identified that although there is a distinction between the authors' predilection regarding which geometry to work on teaching and learning conics, analytical geometry stands out in relation to synthetic geometry. It is thus concluded that the content on Conics still receives a very algebraic treatment in basic education.